Bounce : the myth of talent and the power of practice - Syed, Matthew (London : Fourth Estate, 2011)
In this thoughtful, provocative book, a former Olympian persuasively demonstrates how sports offer powerful and often overlooked tools with which to explore fundamental subjects, including biology, morality, globalization, culture, gender, race, and economics.
Includes bibliographical references and index.
Keywords: Success; Ability; Expertise; Gifted persons; Excellence